228k views
3 votes
Please Help I do not understand what to do.

The table shows values for functions f(x) and g(x) .


x f(x)=4x+1 g(x)=3x+1−4


−3 −11 −359

−2 −7 −113

−1 −3 −3

0 1 −1

1 5 5

2 9 23

3 13 77



What is the solution to f(x)=g(x) ?


Select each correct answer. (multiple answers)





−3


−2


−1


0


1


2


3

2 Answers

1 vote

Answer:

The solution is


f(-1)=g(-1) and
f(1)=g(1).

Explanation:

The given functions are


f(x)=4x+1\\g(x)=3^(x+1)-4

The given table is

x f(x) g(x)

-3 -11 -35/9

-2 -7 -11/3

-1 -3 -3

0 1 -1

1 5 5

2 9 23

3 13 77

As you can observe, the funcitons have the same image at x = -1 and x = 1, there, they are equal y = -3 and y = -1.

Therefore, the equality between these functions is
f(-1)=g(-1) and
f(1)=g(1).

User Emin Israfil
by
5.0k points
5 votes

Answer:

x=1 and x=-1

Explanation:

To find when f(x)=g(x), then look for a value that is the same for both functions in the table. -3 occurs twice for the same x value. 5 also appear twice for the x value 1. This is when they are equal. The solution is (-1, -3) and (1,5).

User Sanusi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.